Using Narrative to Improve Students’ English Reading Skill in School Literacy Movement - Viska Violita; Ouda Teda Ena (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2021)
The objective of this research is to design a set of instructional reading material for the school literacy movement. The reading material developed is expected to support school literacy movement and to improve students’ English reading skill. The reading material designed is based on narrative. Narrative is a sequence of series of events that is fictional and nonfictional that aims to entertain the readers at once to educate the readers about attitudes and behavior through moral values that are contained in the story (Abbot, 2008). The developed material consists of three chapters. These chapters are designed based on the three kinds of narrative text, there are romance, legend, and adventure. Each chapter consists of four parts, namely preparing for the journey, starting the journey, exploring the journey, and finishing the journey. Preparing for the journey part is aimed to activate students’ prior knowledge about the learning topic and to help the students understand the learning material before the students do school literacy movement activity. Starting the journey and exploring the journey parts are designed to develop students’ reading skills and to improve students’ English. Finishing the journey part is aimed to help the students draw the conclusion and master the learning material better. The writers used the research and development method in conducting the study and designing the reading material. Then, the instruments of this research were open-ended questionnaires, close-ended questionnaires, and interview. The English reading material had been evaluated and deemed as very good after the revision. The reading material and the reading tasks are appropriate for school literacy movement activity. By mean of this research, it is expected that the instructional reading material will be beneficial to support the school literacy movement.